KORELASI SPIRITUAL TERHADAP BUDAYA INSTAN - Robingun Suyud El Syam (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2020)
In human life, technological changes occur rapidly. Currently, technological developments can occur in a matter of days. In the beginning, technology was created to assist humans in carrying out their activities. However, other technologies have had a negative impact on human life. The negative impact caused by the development of instant culture information technology. This instant paradigm has made people want to quickly get everything without going through a process. This condition also has an impact on how to treat nature. Technological development is used as a means to exploit nature. The negative influence of this technological development can be overcome by a paradigm shift. However, these changes require courage, so that in the end humans are wise in using technology in their lives. Thus it takes maturity to think so that this can manifest in a person, and spiritual strengthening is multi-key.